2020
DOI: 10.5194/acp-20-3397-2020
|View full text |Cite
|
Sign up to set email alerts
|

Modeling stratospheric intrusion and trans-Pacific transport on tropospheric ozone using hemispheric CMAQ during April 2010 – Part 2: Examination of emission impacts based on the higher-order decoupled direct method

Abstract: Abstract. The state-of-the-science Community Multiscale Air Quality (CMAQ) modeling system, which has recently been extended for hemispheric-scale modeling applications (referred to as H-CMAQ), is applied to study the trans-Pacific transport, a phenomenon recognized as a potential source of air pollution in the US, during April 2010. The results of this analysis are presented in two parts. In the previous paper (Part 1), model evaluation for tropospheric ozone (O3) was presented and an air mass characterizatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

6
2

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Potential vorticity (PV) has been shown to be a robust indicator of air mass exchange between the stratosphere and the troposphere. The value of PV itself generally increases with altitude, and previous studies suggested that a value of 2 PVU (1 PVU = 10 −6 m 2 K kg −1 s −1 ) is an indicator of stratospheric air (Hoskins et al, 1985;Wernli and Bourqui, 2002;Itoh and Narazaki, 2016). Through this study, the tropopause is diagnosed by 2 PVU.…”
Section: Modeling System and Simulation Setupsupporting
confidence: 48%
“…Potential vorticity (PV) has been shown to be a robust indicator of air mass exchange between the stratosphere and the troposphere. The value of PV itself generally increases with altitude, and previous studies suggested that a value of 2 PVU (1 PVU = 10 −6 m 2 K kg −1 s −1 ) is an indicator of stratospheric air (Hoskins et al, 1985;Wernli and Bourqui, 2002;Itoh and Narazaki, 2016). Through this study, the tropopause is diagnosed by 2 PVU.…”
Section: Modeling System and Simulation Setupsupporting
confidence: 48%
“…All available observation data were used in this study. As we have discussed in previous work (Itahashi et al, 2020b), Asian air pollution can impact on air quality over the U.S.A.; however, the magnitude of volcanic emissions on tropospheric SO4 2levels over North America has not been well studied. To evaluate the impact of volcanic SO2 emissions located in the northern hemisphere To evaluate model performance with ground-based observations, the Pearson's correlation coefficient (R) with student's t-test is used for assessing the statistical significance level.…”
Section: Ground-based Observationsmentioning
confidence: 96%
“…The Community Multiscale Air Quality (CMAQ) modeling system version 5.2 extended for hemispheric applications (H-CMAQ) (Sarwar et al, 2015;Xing et al, 2015a;Mathur et al, 2017;Itahashi et al 2020aItahashi et al , 2020b) is used to incorporate and assess the impacts from volcanic SO2 emissions. H-CMAQ is configured to cover the entire Northern Hemisphere, utilizing a polar stereographic horizontal discretization of 187×187 grid points with a grid spacing of 108 km and a terrain-following vertical coordinate system with 44 layers of variable thickness from the surface up to 50 hPa.…”
Section: Hemispheric Cmaq Modeling System and Its Set Upmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate model performance with ground-based observations, the Pearson's correlation coefficient (R) with Student's t test is used for assessing the statistical significance level. The normalized mean bias (NMB) and the normalized mean error (NME) are also calculated as follows (e.g., Zhang et al, 2006;Itahashi et al, 2020b).…”
Section: Ground-based Observationsmentioning
confidence: 99%